Influência dos tratamentos superficiais executados na parede de concreto no desenvolvimento da aderência com revestimentos cerâmicos internos - Patrícia Vasconcelos De Oliveira (2020)
Ceramic detachment is a construction pathological manifestation that occurs due to the lack of adherence between coating layers, that brings several problems to the civil construction sector. This lack of adherence is related to factors such as: substrate characteristics (pore distribution, roughness, absorption and presence of dirt), type of adhesive mortar (percentage of polymeric additives). There are several studies about ceramic tile adhesion on many types of substrates. However, there are few studies related to new construction systems such as concrete wall bonded in place. Considering this scenario, this study aimed to verify the adherence of ceramic tiles layed with industrialized adhesive mortars ACI, ACII and ACIII on concrete wall substrates subjected to different types of surface treatments, which are mechanical sanding followed by hydrojetting (LMH), only hydrojetting (H), manual brushing with detergent followed by hydrojetting (EMDH), and untreated surface (ST). The experimental program first involved treated bases characterization by analyzing the images recorded with digital microscope (1000 times), and checking the roughness and water absorption. Posteriorly, was analysed the pull-off strength of all proposed situations was, as well as the type of rupture and the adhesion extension. It was found that those treatments tend to reduce the presence of mold release oil on the wall and to increase porosity, increasing roughness and water absorption. It was found that the EMDH-ACI, LMH-ACI, ST-ACI, H-ACI and ST-ACII situations presented insufficient results and their use would not be recommended for concrete wall bonded in place system. Finally, it is concluded that the H-ACII situation got excellent results with less effort to carry out bases treatment and its use would be more recommended for laying ceramic tile on concrete walls.